For goodness sake! What is intrinsic value and why should we care?. (May 2017) - Batavia, Chelsea; Nelson, Michael Paul
Abstract: In recent years, conservation planning, policy, and communications have increasingly emphasized the human benefits, or "ecosystem services, " provided by nonhuman nature. In response to this utilitarian, anthropocentric framing, some conservationists have countered that nonhuman nature is valuable for more than its instrumental use to humans. In other words, these critics maintain that nonhuman nature has intrinsic value, which the ecosystem services paradigm fails to duly acknowledge. Proponents of the ecosystem services approach have responded in turn, either by proposing that intrinsic value can be integrated into the ecosystem services framework, or by justifying the pull away from intrinsic value on the grounds that it does not motivate broad support for conservation. We suggest these debates have been clouded by an ambiguous conceptualization of intrinsic value, which in fact has a rich intellectual heritage in philosophy and environmental ethics. We therefore review some of the major work from these literatures, to provide members of the conservation community with a deeper understanding of intrinsic value that, we hope, will inform more focused and productive discourse. Following this review, we highlight two common ways intrinsic value has been misinterpreted in recent debates around ecosystem services. As a result of these misinterpretations, we argue, the non-anthropocentric ethical concerns raised by many critics of the ecosystem services approach remain effectively unaddressed. We conclude by offering logical, practical, and moral reasons why the concept of intrinsic value continues to be relevant to conservationists, even and especially in the emerging ecosystem services paradigm. Highlights: Intrinsic value has a rich intellectual history in philosophy/environmental ethics. The concept of intrinsic value is being mishandled by many conservationists. Intrinsic value is not captured by utilitarian measures of instrumental value. Moral claims about nonhuman intrinsic value are not primarily meant to "work." Intrinsic value matters to conservationists for at least three distinct reasons.